2014
DOI: 10.5267/j.msl.2014.4.010
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the effect of cognitive emotion regulation strategies on job satisfaction

Abstract: This paper examined the effects of cognitive emotion regulation on employees' job satisfaction. In this survey, Questionnaire and the questions were divided into two categories of cognitive emotion regulation and job satisfaction. To measure cognitive emotion regulation, including unadjusted emotion regulation strategies and adjusted strategies, 36 items questionnaire was used originally developed by Garnefski et al. (2001) [Garnefski, N., Kraaij, V., & Spinhoven, P. (2001. Negative life events, cognitive emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The present study supports the effectiveness of emotion regulation on emotional intelligence and subscales (selfmanagement, self-awareness, relationship management, and social awareness) in students with hearing impairment. The result of the present study was consistent with the study results of Shahba, Alvani, Zahedi, and Memarzadeh, who reported that the cognitive emotion regulation strategies improved job satisfaction of subjects [23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study supports the effectiveness of emotion regulation on emotional intelligence and subscales (selfmanagement, self-awareness, relationship management, and social awareness) in students with hearing impairment. The result of the present study was consistent with the study results of Shahba, Alvani, Zahedi, and Memarzadeh, who reported that the cognitive emotion regulation strategies improved job satisfaction of subjects [23].…”
Section: Discussionsupporting
confidence: 92%
“…The research investigated the effectiveness of cognitive emotion regulation on the job satisfaction of employees. The results revealed that the strategies of cognitive emotion regulation improve the job satisfaction of subjects [23]. The results of the study showed who people with high emotional intelligence form their emotions.…”
Section: Introductionmentioning
confidence: 85%
“…Stress is an affective, cognitive, behavioral and mental reaction to harmful aspects of work and workplace [41] [54]. Generally, job stress can be considered as a response to work-related pressures that happens when expectation from someone is beyond his capability and authorization [46] [52]. In this respect, our findings indicated that there is a significant relationship between life orientation and job stress.…”
Section: Conclusion and Discussionmentioning
confidence: 64%
“…In this respect, organizations should select employees with Furthermore, programs focused on employee development can enhance such skills through training programs and workshops (Demirtas et al [33]). Shahba et al [46] investigated the effect of cognitive emotion regulation strategies on job satisfaction. Their results showed that the adjusted cognitive emotion regulation as stress coping strategies will lead to increase in job satisfaction of employees while unadjusted cognitive emotion regulation strategies will reduce their' job satisfaction.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In its entirety, symptom reduction post-therapy is demonstrably associated with improvements in emotion regulation adaptive strategies (Aldao et al, 2014). Evidence shows that cognitive emotion regulation programs have significant effects on anxiety and depression (Aldao et al, 2010), emotional intelligence (Peña-Sarrionandia et al, 2015), job satisfaction (Shahba et al, 2014), social sharing (Bucich & MacCann, 2019), emotion regulation difficulties and alexithymia (Schoorl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%